(untitled) (World Bulletin of Social Sciences, 2023)
It is known that in the process of communication, speakers and writers use their existing knowledge and experience in linguistics to explain their content to the interlocutor, to provide him with the necessary information. They strive to make effective use of figures of speech. This article explains theory of tropes and figures of speech and problem of hyperbole in contemporary cognitive linguistics